Q: -2x plus 16 equals 0

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

8x + 16 = 6x -> 2x + 16 = 0 -> 2x = -16 -> x = -8

x = 8 and y = 0

3x2 + 2x = 16 ∴ 3x2 + 2x - 16 = 0 ∴ 3x2 - 6x + 8x - 16 = 0 ∴ 3x(x - 2) + 8(x - 2) = 0 ∴ (3x + 8)(x - 2) = 0 ∴ x ∈ {-8/3, 2}

2(x - 2)(x - 4)

many solutions

Related questions

8x + 16 = 6x -> 2x + 16 = 0 -> 2x = -16 -> x = -8

x=0

x = 8 and y = 0

x = 0

2x + 4y = 16 <=> 2x + 4y - 16 = 0 2x - 4y = 0 2x - 4y = 2x + 4y - 16 -8y = -16 y = 2 Substituting the known value for y in either of the original equations enables x to be determined. 2x + (4*2) = 16 : 2x = 16 - 8 : x2x = 8 : x = 4 2x - (4*2) = 0 : 2x - 8 = 0 : 2x = 8 : x = 4. The ordered pair satisfying both equations is (4,2)

2x = -7 - 8y

If -2x +14 = 0, -2x = -14, or x = 7.

3x2 + 2x = 16 ∴ 3x2 + 2x - 16 = 0 ∴ 3x2 - 6x + 8x - 16 = 0 ∴ 3x(x - 2) + 8(x - 2) = 0 ∴ (3x + 8)(x - 2) = 0 ∴ x ∈ {-8/3, 2}

Assuming that 4x2+2x = 0: 2x (2x+1) = 0 2x = 0 or 2x+1 = 0 x = 0 or -1/2

2(x - 2)(x - 4)

y = 0 and x = 8.

many solutions